Green human resource management : a sustainable approach to human capital development in the contemporary workplace. - Casignia, Joana Marie F. Entereso, Louise Alexandra T. Elento, Jethro R. Ramirez, Honey G.E. Macaraig, Jean Luisa B. Valerio, Regine T. Velasco, Ernalyn H. 4 0 16; 5
ABSTRACT This paper was conducted in November 2024 in companies within Metro Manila. This study aims to understand the eMects and relationship of the implementation of Green Human Resource Management on the Human Capital Development of a company. It utilized a quantitative approach using a descriptive-correlational. Has a total of 51 respondents that are current Human Resource Practitioners were chosen using a purposive sampling technique. The research instrumentation used was a survey-based assessment tool namely Google Forms that contained Three sections with a total of 47 questions utilizing both multiple choice questions and 4-point Likert Scale.
Business Research: (BSBA major in Human Resource Management) - Pamantasan ng Lungsod ng Maynila, 2024.
Keywords: 2 -- 0; 6; 20; 20; 2